Analisis Sistem Reward dan Punishment untuk Meningkatkan Motivasi Kerja dan Organizational Commitment Karyawan dengan Studi Kasus Pada PT XYZ [Analysis of Reward and Punishment to Increase Work Motivation and Organizational Commitment of Employees at XYZ Company] - Christie, Olivia Brenda; Kui, Daniel Ong Kim; Huliselan, Juanna Judith (Feedforward: Journal of Human Resource, 2022)
This study aims to determine the effect of reward and punishment on work motivation and organizational commitment of employees at PT XYZ company. This study uses quantitative methods and non-probability sampling techniques, where samples taken using purposive sampling totalling 130 employees. Data was collected using a questionnaire with a Likert scale which was then analyzed using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) technique on SmartPLS 3.0 software. The results of the study prove that organizational commitment has no effect on employee motivation and performance, while employee empowerment and reward and punishment have a positive influence on employee motivation and performance. The importance of implementing employee empowerment and reward and punishment will create a high level of motivation and performance for employees if it is carried out according to employee expectations.Bahasa Indonesia Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh reward dan punishment terhadap motivasi kerja dan komitmen organisasi karyawan pada perusahaan PT XYZ. Penelitian ini menggunakan metode kuantitatif dan teknik non-probability sampling, di mana sampel yang diambil menggunakan purposive sampling yang berjumlah 130 karyawan. Pengumpulan data dilakukan menggunakan kuesioner dengan skala Likert yang kemudian dianalisis menggunakan teknik Partial Least Squares - Structural Equation Modeling (PLS-SEM) pada software SmartPLS 3.0. Hasil penelitian membuktikan bahwa komitmen organisasi tidak berpengaruh terhadap motivasi dan kinerja karyawan, sedangkan employee empowerment serta reward dan punishment memiliki pengaruh positif terhadap motivasi dan kinerja karyawan. Pentingnya implementasi employee empowerment dan reward dan punishment akan menciptakan tingkat motivasi dan kinerja yang tinggi terhadap karyawan jika dilakukan sesuai harapan karyawan.